Implementasi Sistem Pengendalian Intern, Transparansi dan Penerapan Aplikasi Sistem Keuangan Desa (Siskeudes) pada Akuntabilitas Keuangan Desa - Putu Putri Prawitasari; Made Ratih Nurmala Sari; Ayu Indira Dewiningrat; Ni Putu Ari Krismajayanti (Syntax Idea)
The realization of village financial management accountability is related to the existence of internal control, transparency and implementation of the Application Siskeudes. The purpose of the study was to determine the effect of internal control, transparency and the application of the Village Financial System Application (Siskeudes) on village financial accountability. The research to be carried out is a descriptive research type and uses a quantitative approach that describes the behavior of respondents regarding the influence of the Internal Control System, Transparency, and Application SISKEUDES on Village Financial Accountability in Badung Regency, Bali. The technique used in sampling in this study is a convenience sampling technique. The results showed that internal control, transparency and application Siskeudes had a positive effect on village financial accountability. The better the internal control, transparency and implementation Siskeudes, the higher the accountability of village finances. The importance of research results as an evaluation material for the village apparatus of Badung Regency in particular and the community regarding how the management is accountable so that it can create prosperity for the public interest.